Calculation model for surface roughness of face gears by disc wheel grinding. (December 2017) - Wang, Yanzhong; Liu, Yang; Chu, Xiaomeng; He, Yueming; Zhang, Wei
Abstract: Face gears have been widely used in the transmission systems of aviation and vehicle as a new form of transmission. In order to improve the bearing capacity and reliability of face gears, it is necessary to study the grinding surface roughness of face gears, so as to guide the grinding process of face gears. A mathematical model of roughness based on disc wheel grinding for face gears is proposed. The model can calculate tooth surface roughness based on grinding machining principle of face gear by disc wheel, considering roughness caused by material removal by grinding wheel wear and the discretized generating movement between grinding wheel and workpiece. Supported by the proposed model, the distribution of surface roughness of face gear is analyzed. The model is verified by experimental data, the influence of grinding parameters on the surface roughness is summarized, and the grinding optimization scheme is put forward. Graphical abstract: Highlights: A mathematical model of grinding roughness for face gears is proposed. The model is built based on face gear machining mechanism and grinding mechanism. The distribution of roughness on tooth surface can be obtained through the model. The influence of grinding parameters on roughness of tooth surface is analyzed.